A Spatial Study of the Location of Superfund Sites and Associated Cancer Risk. Issue 1 (1st January 2018) - Amin, Raid; Nelson, Arlene; McDougall, Shannon
ABSTRACT: Superfund sites are geographic locations selected by the U.S. Environmental Protection Agency as having extreme toxic chemical spills. In this article, we address three main research questions: (1) Are there geographical areas where the number (or density) of Superfund sites is significantly higher than in the rest of the USA? (2) Is there an association between cancer incidence and the number (or density) of Superfund sites? (3) Do counties with Superfund sites have higher proportions of minority populations than the rest of the USA? We study the geographic distribution of the overall cancer incidence rate (2007–2011) in addition to the geographic variation of Superfund sites for 2013. We used the disease surveillance software package SaTScan with its scan statistic to identify locations and relative risks of spatial clusters in cancer rates and in Superfund site count and density. We also used the surveillance software FlexScan to support and complement the results obtained with SaTScan. We find that geographic areas with Superfund sites tend to have elevated cancer risk, and also elevated proportions of minority populations.